The Use of Politeness Strategies in Maintaining Unbiassed Statements in El Clasico Match Commentary: English - Faradilla Hasby Aulia; Andang Saehu; Dian Budiarti (Prodi Tadris Bahasa Inggris, 2025)
The ability to maintain unbiassed in football match commentary can be influenced by politeness strategies, which are a part of communication strategies. These strategies create a good relationship between the commentator and the audience, and also make the delivery of criticism or analysis more neutral and respectful. Nevertheless, there is a lack of research focusing on the effects of politeness strategies on objectivity in the sports domain, particularly in highly competitive matches or stressful situations, as previous studies examining politeness strategies have generally addressed the context of everyday communication. The reasearch aims to evaluate the effectiveness of politeness strategies in maintaining bias during commentary in football matches. This study used Brown and Levinson's Politeness Strategies theory and John C. Merrill's journalist ethical principles. This research used a descriptive qualitative method with data analysis of match commentary transcripts. The results showed that the application of politeness strategies can maintain the objectivity of statements made during football match comments because in politeness strategies there is an attitude of respect for both parties involved in communication and does not show partiality to any party and does not put pressure on anyone without reducing the quality of the analysis delivered.